Transformative pedagogy fostering student character through discipleship communities at HKBP nommensen university - Udur Ernita Aritonang; Vornalita Pelsa Sambalao; Dirk Roy Kolibu (Journal of Educational and Learning Studies, 2026)
This study examines the implementation of transformative pedagogy in Christian Religious Education (CRE) through discipleship communities to foster holistic student character formation in Christian higher education. A qualitative literature review was conducted using a theological-pedagogical hermeneutic approach. Data were collected from peer-reviewed journal articles, books, biblical texts, and theological documents related to transformative pedagogy, discipleship, and Christian character formation. The data were analyzed through literature selection, thematic analysis, and theological-pedagogical synthesis. The findings indicate that discipleship communities provide a structured, relational, and faith-based learning environment that effectively integrates theological learning, spiritual growth, moral development, and character formation. Discipleship communities should be recognized as an integral pedagogical model in Christian Religious Education, offering a transformative framework that systematically integrates theological knowledge, character formation, and missional practice to strengthen Christian higher education.